The limitations of international law at the Eritrea-Ethiopia Claims Commission and its implications for future conflict. Issue 4 (2nd October 2021) - Campbell, John R.
ABSTRACT: This paper examines the litigation strategies adopted by Eritrea and Ethiopia before the Eritrea-Ethiopia Claims Commission convened at The Permanent Commission of Arbitration at The Hague between 2001 and 2009. I pursue insights from the work of Laura Nader concerning how, through binding arbitration, the international community imposes its power on disputing parties as opposed to allowing their competing legal claims to be fairly decided. The claims examined by this paper concern who started the border war and that Ethiopia denationalized 'Eritrean' nationals and unlawfully deprived them of their property. I conclude that the PCA's decisions on Eritrea and Ethiopia were flawed and that its deliberations need to be viewed in a much wider political context; furthermore its decisions contributed to further political instability in the Horn of Africa.